OPTIMALISASI PERAN TEKNOLOGI DALAM SUPERVISI PENDIDIKAN - Eni Sofiatunnaimah; Ahmad Manshur (Lembaga Penelitian, Penerbitan dan Pengabdian kepada Masyarakat (LP3M) IAIFA Kediri, 2025)
This study aims to analyze the optimal implementation of educational supervision using Artificial Intelligence (AI) to improve the quality of learning in elementary schools. The research employs a library research approach by reviewing various relevant literatures such as books, scientific journals, papers, and policy documents. The findings reveal that most Islamic educational institutions still apply traditional curricula that focus on memorization and normative mastery of religious materials, which do not fully support 21st-century skills such as digital literacy and critical thinking. Furthermore, AI contributes to enhancing transparency and enables more data-driven planning for teachers’ professional development. However, several challenges remain, including inadequate technological infrastructure, limited skilled human resources, and concerns regarding data privacy that need to be addressed. These findings indicate that AI holds great potential to transform the way educational supervision is conducted, but its success depends on the readiness and supportive policies of educational institutions. The study recommends the importance of training for education practitioners, strengthening technological infrastructure, and developing data privacy policies to ensure that the implementation of AI in educational supervision can run effectively and sustainably.